Environment friendly management of mosquito: a short review - Riaz, MA; Riaz, A; Ijaz, B; Rasool, MS; Rahat, S; Nisa, Z Un (Bangladesh Journal of Scientific and Industrial Research, 2018)
Despite the large scale use of insecticides, capacity building, municipality, community and metropolis awareness, and preventive measures to counter vector borne diseases which are mounting day-by-day, new tools are now been introducing to prevent the spread of mosquito transmitted diseases. The low efficacy status of chemical pesticides have lead to the interest of researchers in search of fresh and even more practicable vector control methodologies to be applied. In this regards, multiple alternatives have been monitoring to develop control practice measures for the eradication, observation and control of mosquitoes at larval level by the use of a sustainable biological monitoring and control by an ordinary constructive predator, to exercise monitoring and practical control measures over parasites at larval stages in environmental and eco-friendly techniques. In particular, bio-control measures to monitor and control practical practices, context predatory larvivorous fish, dragonfly nymph, frogs, copepods, turtle, Entomopathogenic bacillus, Bacillus sphaericus and Bacillus thuringiensis israelensis are beings tried in different regions of world. The available research on the subject recommends that there exist multiple direct and indirect growth factors that could play a dynamic role in prey and predator’s survival. Species controphic that have an impact on concerned eco-relation reflect significant effect. In addition to this, certain eco-relations represent positive stimuli for the control of vector borne viral diseases. As a bio-control achieving feasible agent for vector monitoring, pointing, management and control predatory larvivorous fish, dragonfly nymph, frogs, copepods, turtle, Entomopathogenic bacillus, Bacillus sphaericus and Bacillus thuringiensis israelensis are not only considered as a liberated intervention for disease vector control of practices and mechanical control cost deterrents as well. Further research has been suggested on the subject so as to find out even more practicable and effective mosquito monitoring and practical control practices. Bangladesh J. Sci. Ind. Res.53(3), 169-178, 2018